Polybenzimidazole thermal management composites containing functionalized boron nitride nanosheets and 2D transition metal carbide MXenes. (28th September 2019) - Liu, Zhong-Jie; Yin, Chuan-Gen; Cecen, Volkan; Fan, Jin-Chen; Shi, Peng-Hui; Xu, Qun-Jie; Min, Yu-Lin
Abstract: Recently, polymer-based thermal management materials have been receiving more and more attention. Always, introducing the thermal conductive nanofillers to prepare polymer composites is one of the best ways to improve the thermal conductivity (TC) of the polymer. However, the simple and effective way to improve thermal conductivity by increasing fillers loading amount often brings the decrease of mechanical property resulted by agglomeration. Herein, we combined 2D transition metal carbides (Ti3 C2 Tx ), and functionalized boron nitride nanosheets (f-BNNS) together for simultaneously enhancing the TC and mechanical property of polybenzimidazole (PBI)-based composites. As the loading amounts of f-BNNS-Ti3 C2 Tx reached 25 wt% (f-BNNS: 12.5 wt%, Ti3 C2 Tx : 12.5 wt%), the in-plane and through-plane TCs of the f-BNNS-Ti3 C2 Tx /PBI composite film reach ~5.06 and ~3.44 W m −1  K −1 which are ~12.05 and ~8.19 times higher than those of neat PBI film. More notably, the synergistic effect of interspace-filling and bridging between f-BNNS and Ti3 C2 Tx also prevents the agglomeration and facilitates the improvement of mechanical property, even at a high loading amount of 25 wt%, the yield and ultimate tensile strengths of f-BNNS-Ti3 C2 Tx /PBI composite film are ~175.5 and ~189.6 MPa with increases of ~61.1% and ~39.8% compared to those of neat PBI. Graphical abstract: Image 1 Highlights: f-BNNS and Ti3 C2 Tx were introduced into a PBI matrix together. f-BNNS-Ti3 C2 Tx /PBI exhibits high thermal conductivity and good mechanical property. There are strong interactions among f-BNNS, Ti3 C2 Tx, and PBI. The synergistic effect between f-BNNS and Ti3 C2 Tx favors the improvement of thermal conductivity and mechanical property.